The development of a mindful eating app for adolescents through mixed-methods feedback from adolescents with overweight or obesity - Serrano-Gonzalez, Monica; Triedman, Miranda; Mandapati, Amiya; Tanzer, Joshua Ray; Rosen, Rochelle; Jelalian, Elissa; Jandasek, Barbara (Frontiers in Adolescent Medicine, 2025)
IntroductionObesity in childhood and adolescence continues to be a major public health challenge. Mindfulness-based interventions (MBIs) can be great adjuvants to multidisciplinary weight management interventions for adolescents. Delivery of MBI via mobile phones can decrease barriers to engagement. Mindfulness increases present-moment awareness, which may promote self-regulation, which is in turn important for weight management. Several studies have shown that delivering mindfulness training for adolescents via mobile devices may be feasible and acceptable, but this is still a growing area of research. The Unified Theory of Acceptance and Use of Technology (UTAUT) is a framework that has been used to understand why individuals choose to use health apps. This study aims to gather adolescent perceptions about an existing mindful eating mobile app designed for adults, via mixed methods research, and to utilize their feedback to design and develop a mindful eating app for adolescents.MethodsThis was a cross-sectional, mixed methods study. Twenty-five adolescents, 13–17 years old, with a BMI ≥ 85th percentile completed a UTAUT-based survey and a semi-structured interview after viewing excerpts from an existing mindful eating mobile app.ResultsAdolescents with overweight/obesity are receptive to using a mindful eating app, with some concerns about Effort Expectancy and Self-Efficacy. Youth endorse that such an app should have reminders, short and colorful videos with captions, and it should be engaging, relatable, and non-judgmental. This information was used to develop a mindful-eating web-based app for adolescents, SAMBA (Study of an Adolescent Mindfulness-Based App).ConclusionsWe developed a mindful eating web-based app for adolescents utilizing feedback from this youth cohort using an existing mobile app as the starting point. Future directions include pilot testing the app and its content.